A numerical study on the effects of naturally ventilated shaft and fire locations in urban tunnels. (27th August 2019) - Fan, Chuangang; Chen, Jian; Mao, Zhanli; Zhou, Yang; Mao, Shaohua
Summary: In more and more tunnels, natural ventilation mode with vertical shafts has been gradually employed. However, there are few studies investigating the influences of fire and shaft positions on natural ventilation performance currently. Therefore, this study investigated the effects of the transverse distance from fire source to tunnel sidewall, the longitudinal distance from fire source to shaft, and the transverse distance from shaft to sidewall on natural ventilation effectiveness in a tunnel fire by using Fire Dynamics Simulator. The typical characteristic parameters of smoke, such as mass flow rate, temperature distribution, and velocity vector were analyzed; besides, the phenomenon of plug‐holing was discussed. The results have shown that the mass flow rate of gas exhausted by the shaft decreases slightly with the increase of longitudinal distance from fire source to shaft. When the longitudinal distance from fire source to shaft is constant, changing the transverse distance from shaft to sidewall will have a more obvious effect on the effectiveness of exhausting smoke than changing the transverse distance from fire source to sidewall; in addition, the phenomenon of plug‐holing is more serious when the shaft is close to the sidewall.